New combinations and lectotypifications in Distimake Raf. (Convolvulaceae) - Petrongari, Fernanda Satori; Simões, Ana Rita; Simão-Bianchini, Rosângela (Phytotaxa, 2018)
As a result of recent molecular and morphological evidence (Simões et al. 2015), Merremia Dennstedt ex Endlicher (1841: 1403) was recircumscribed, and most of the species transferred to Camonea Rafinesque (1838: 81), Decalobanthus Ooststroom (1936: 99) and Distimake Rafinesque (1838: 82) by Simões & Staples (2017). During our studies of Distimake and Merremia s.l. from America, we noted that nine species and two varieties that had not been transferred to Distimake clearly fitted Distimake as proposed by Simões & Staples (2017) by possessing the following characters: compound or deeply lobed leaves (exceptionally entire leaves occur), calyces with sepals appressed to the corolla, white or yellow, glabrous corollas, and tricolpate pollen. In the context of our ongoing taxonomic studies in the genus Distimake, the formal transfer of a number of species into this genus is necessary. Lectotypes are designated following the International Code of Nomenclature (ICN) (McNeill et al. 2012).